A method for predicting the polymerization degree of a solidified electrode plate prepared by a polymer monomer homogenate method and application thereof
Patent Information
- Application Number
- CN202611130590.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
工艺人员多依赖经验调整,难以实现精准、可重复的工艺控制
[0050]1、 本发明创造性地建立了聚合程度与孔隙率(ε)、聚合物单体添加量(X)、极片初始压实密度(C)、真密度(TD)、聚合物单体密度系数(P)及厚度变化(ΔT)等关键可测量制备参数之间的定量数学公式。不需要复杂的直接化学分析,仅利用极片制备过程中及完成后易于常规获取的物理参数,即可实现对极片内部核心状态变量-聚合程度的精准、便捷预测。
Smart Images

Figure CN123017265A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery electrode materials and battery performance prediction technology, and particularly to a method for predicting the degree of polymerization of solidified electrodes prepared by polymer monomer homogenization and its application. Background Technology
[0002] Polymer solid-state batteries, especially those based on solid-state electrodes formed by polymer monomer polymerization, are highly dependent on the quality and uniformity of the polymerization reaction. The most direct influencing factor is the degree of polymerization. The degree of polymerization directly reflects the content of residual monomers, and this parameter is directly related to the side reactions, interfacial impedance, electrode mechanical strength, and safety stability of the solid-state battery prepared from that electrode. Therefore, accurately assessing and controlling the degree of polymerization within the solid-state electrode is a core step in ensuring the electrochemical performance and reliability of the battery.
[0003] Currently, direct and accurate detection of the polymerization degree of solid-state electrodes faces significant technical challenges, and commonly used chemical analysis methods are complex to operate. Furthermore, because the polymerization reaction is affected by various factors such as temperature field, initiator distribution, and precursor penetration depth, the polymerization degree inside the electrode (from the surface to the current collector interface, from the center to the edge) may have a gradient distribution, making it difficult for point sampling or surface measurements to reflect the overall situation.
[0004] Current technologies lack effective models for quantitatively predicting the degree of polymerization within the electrode based directly on measurable preparation parameters (such as monomer feed rate, electrode thickness, and porosity). Process engineers often rely on experience for adjustments, making precise and repeatable process control difficult. Furthermore, the inability to conveniently and accurately obtain the key internal state variable of the degree of polymerization hinders closed-loop optimization of the solid-state process. This makes it difficult to systematically establish the relationship between the degree of polymerization, microstructure, and macroscopic electrochemical performance during battery development, thus impeding rapid material screening and efficient system development.
[0005] Because the polymerization reaction occurs within the complex three-dimensional porous structure of the electrode, the electrode's microstructure, such as porosity and pore distribution, reflects the filling and distribution of polymer monomers. Different monomer feed rates and coating thicknesses will also produce different polymerization kinetics, leading to different polymer network morphologies and degrees of polymerization. This makes the degree of polymerization closely coupled with the initial physical state of the electrode and the preparation process parameters.
[0006] Therefore, developing a predictable method for evaluating the degree of polymerization, particularly establishing a predictive model based on readily available electrode preparation parameters and initial physical properties, is of crucial industrial and scientific value. This paper provides a novel and practical technical solution to address the aforementioned challenges, enabling early prediction and precise control of the quality of solid-state electrodes in polymer solid-state batteries, thereby improving overall battery performance and manufacturing capabilities, and accelerating the industrialization of polymer solid-state batteries. Summary of the Invention
[0007] This invention addresses the shortcomings of existing technologies, such as the complexity of detecting the polymerization degree of solid-state electrodes and the lack of methods to predict battery electrochemical performance based on relevant parameters of solid-state electrodes before battery fabrication. This invention aims to establish a quantitative correlation model between the polymerization degree and key parameters such as the porosity of solid-state electrodes, the amount of polymer monomer added, and electrode thickness variation. This provides a method for predicting the polymerization degree of solid-state electrodes prepared by polymer monomer homogenization. This method accurately predicts the polymerization degree of solid-state electrodes based solely on their porosity, combined with other conventional physical characteristics and preparation parameters. Furthermore, it can predict the specific capacity of the main cell material and electrode swelling, providing a more accurate method for evaluating the electrochemical performance of cells assembled from solid-state electrodes. This contributes to the performance prediction and development of solid-state electrodes with excellent electrochemical performance, providing crucial technical support for the development of solid-state batteries.
[0008] The applicant discovered in their research that by anchoring key parameters affecting porosity, a predictive correlation could be established between porosity and the degree of polymerization. By establishing a mapping relationship between the degree of polymerization N and the electrode porosity ε, the applicant developed the following electrode porosity screening model based on the degree of polymerization N, including the following steps:
[0009] S1: The mass fraction of uncured polymer monomers in the extraction solution is obtained by extracting the solidified electrode sheet;
[0010] S2: Calculate the degree of polymerization N of the solidified electrode based on the mass fraction of the uncured polymer monomers obtained in S1;
[0011] When solidified electrodes are prepared using polymer monomer coating / polymer monomer immersion, the degree of polymerization N of the solidified electrodes is calculated using the following formula (F1);
[0012] , formula (F1);
[0013] When solidified electrodes are prepared using the polymer monomer slurry addition method, the degree of polymerization N of the solidified electrodes is calculated using the following formula (F2);
[0014] , formula (F2);
[0015] Where W0 is the mass of the pre-coated / immersed polymer monomer electrode; W1 is the mass of the solidified electrode; W2 is the mass of the extraction solvent; mi is the mass fraction of uncured polymer monomer in the extraction solution characterized by gas chromatography-mass spectrometry after each extraction; n is the number of extractions; C2 is the areal density of the solidified electrode; A is the solvent volatility coefficient, which is the ratio of the mass of the extraction solvent that evaporated to the mass of the extraction solvent after being placed in a sealed box for 5 days at 1 standard atmosphere at room temperature; S is the area of the solidified electrode cut out; X is the ratio of the mass of polymer monomer added to the total mass of active material, conductive agent and binder added when preparing the solidified electrode;
[0016] S3: Calculate the predicted porosity ε of the solidified electrode based on the degree of polymerization N obtained in S2, combined with the physical characteristics and preparation parameters during the solidified electrode preparation process.
[0017] When solidified electrodes are prepared using polymer monomer coating / polymer monomer immersion methods, the predicted porosity ε of the solidified electrode is calculated using the following formula (F3):
[0018] , formula (F3);
[0019] When solidified electrodes are prepared using the polymer monomer slurry addition method, the predicted porosity ε of the solidified electrode is calculated using the following formula (F4):
[0020] , formula (F4);
[0021] Wherein, the degree of polymerization N is calculated as the ratio of the mass of the polymer monomer solidified in the solidified electrode to the mass of the polymer monomer remaining on the electrode after coating / soaking / slurry addition; the polymer monomer density coefficient P is the density ratio of the polymer monomer to poly(ethylene glycol) diacrylate at a temperature of 25°C; where L is the theoretical polymer monomer feed amount, which is the ratio of the theoretical polymer monomer areal density after coating / soaking to the areal density of the active material, conductive agent, and binder when the electrode is not coated / soaked; C is the compacted density of the electrode before coating / soaking / slurry addition; TD is the true density of the electrode before coating / soaking / slurry addition; and ΔT is the change in electrode thickness before and after coating / soaking / slurry addition.
[0022] The unit of measurement for C2 is g / cm³. 2 The unit of measurement for S is cm. 2 The units for W0, W1, and W2 are g; the unit of measurement for C is g / cm³. 3 The unit of measurement for TD is g / cm³.3 The unit of measurement for △T is μm.
[0023] Therefore, the above correspondence provides a good correspondence verification for the present invention. A reverse strategy can be adopted to predict the degree of polymerization by measuring the porosity, thereby obtaining a method for predicting the degree of polymerization of solidified electrodes prepared by polymer monomer homogenization.
[0024] This invention is achieved through the following technical solution:
[0025] In a first aspect, the present invention provides a method for predicting the degree of polymerization of solidified electrodes prepared by a polymer monomer homogenization method, wherein the method for predicting the degree of polymerization of solidified electrodes is to calculate the predicted value N of the degree of polymerization of solidified electrodes using the following formula (1):
[0026] , formula (1);
[0027] Where X is the amount of polymer monomer added, which is the ratio of the mass of polymer monomer added to the total mass of active material, conductive agent and binder in the preparation of solidified electrode sheet; C is the compacted density of the electrode sheet before the polymer monomer is added to the slurry (which can also be understood as the compacted density of the electrode sheet without polymer monomer added to the slurry); TD is the true density of the electrode sheet before the polymer monomer is added to the slurry (which can also be understood as the true density of the electrode sheet without polymer monomer added to the slurry); ΔT is the change in electrode sheet thickness before and after the polymer monomer is added to the slurry (which can also be understood as the change in electrode sheet thickness without polymer monomer added to the slurry); ε is the porosity of the solidified electrode sheet, and the polymer monomer density coefficient P is the density ratio of polymer monomer to poly(ethylene glycol) diacrylate at a temperature of 25°C.
[0028] The unit of measurement for C is g / cm³. 3 The unit of measurement for TD is g / cm³. 3 The unit of measurement for △T is μm.
[0029] The compaction of conventional cathode materials has applicable ranges and commonly used empirical values, which are calculated by the ratio of the areal density to the thickness of the electrode sheet; the true density of the electrode sheet before the polymer monomer is added to the slurry can be obtained through conventional tests in this field.
[0030] This invention innovatively proposes a method for predicting the degree of polymerization in the preparation of solidified electrodes using a polymer monomer homogenization method. Based on the porosity and other characteristics of the solidified electrode, this invention achieves accurate prediction of the degree of polymerization. This prediction provides an expected basis for battery electrochemical performance, such as swelling, and offers scientific guidance for battery preparation and finished product performance prediction. The degree of polymerization of the polymer is an important parameter in electrode solidification, influenced by multiple factors. There is a dynamic balance relationship between the degree of polymerization, porosity, electrode thickness, and the amount of polymer monomers fed. The porosity of the cured electrode is a direct manifestation of the degree of polymerization, directly reflecting the microscopic changes after curing. The ratio of the compacted density C of the electrode before the addition of polymer monomers to the true density TD of the electrode before the addition of polymer monomers, used in formula (1) of this invention, reflects the porosity ratio of the electrode before the addition of polymer monomers. This ratio reflects that the pores of the electrode before the addition of polymer monomers provide corresponding filling space for the polymer monomers, which to some extent also affects the subsequent polymerization effect. The monomer addition amount X in the formula affects the monomer concentration in the electrode, which in turn directly affects the degree of monomer polymerization. Simultaneously, it is related to the pore capacity formed by the pore ratio before adding the polymer monomer to the slurry. Furthermore, this invention introduces the polymer monomer density coefficient P, which, based on the specific characteristics of the electrode slurry and polymer monomer slurry used in the polymer monomer slurry method, considers the influence of the polymer monomer density coefficient on the physical characteristics of the slurry and its impact on the structural characteristics of the polymer under slurry conditions. In addition, the change in electrode thickness reflects the differences in the preparation method, and it, along with the feeding amount, affects the basis and state of polymer monomer feeding. Under different polymer monomer feeding amounts and changes in electrode thickness before and after coating, the degree of monomer polymerization is significantly affected. Based on the above, this invention establishes a formula relationship by using common fitting methods (such as establishing multi-order equations) to combine the initial pore state of the electrode. Based on the influence of electrode slurry and polymer monomer homogenization on the physical characteristics of the homogenization in the polymer monomer homogenization method, the differences in preparation methods under the changes in polymer monomer feeding amount and electrode thickness, and combined with the final pore state, the degree of polymerization of the solidified electrode can be accurately predicted.
[0031] In this invention, formula (1) is the result of reverse exploration of formulas (F1) to (F4), and the establishment process of formulas (F1) to (F4) is applicable to 2.8 g / cm³. 3 ≤C≤3.6 g / cm 3The selectable range is 70%≤N≤99%, 0≤L≤20%, 0≤X≤25%. Within this range, more accurate data is obtained, avoiding discrepancies between the actual electrode loading amount and the pre-coating compaction density, as well as prediction deviations under extremely unreasonable conditions. This range can also be used as boundary conditions input into the fitting software during the establishment of formula (1) to obtain the fitting equation. Correspondingly, the applicable selectable range for formula (1) is 2.8 g / cm³. 3 ≤C≤3.6 g / cm 3 , 0%<ε≤30%, 0≤X≤25%.
[0032] As a further option, X in formula (1) can be obtained by the weightlessness method, specifically including the following steps:
[0033] SS1: During the homogenization process, a prepolymer solution containing polymer monomers and initiators is added to the electrode slurry for homogenization to obtain a slurry containing polymer monomers. The slurry containing polymer monomers is then uniformly coated onto the current collector. After polymerization, a solidified electrode is obtained and weighed.
[0034] The positive electrode sheet is produced by uniformly coating the electrode slurry onto the current collector, drying it, and then rolling it to produce a conventional electrode sheet, which is then weighed.
[0035] SS2: Both solid-state electrode and conventional electrode were heated from room temperature to 600℃ at a rate of 10℃ / min under an inert gas atmosphere, and weighed separately;
[0036] The weight loss of the conventional electrode is obtained by the difference between the mass of the conventional electrode after heating to 600℃ and the mass of the conventional electrode. The weight loss rate t1 of the conventional electrode is obtained by the ratio of the weight loss of the conventional electrode to the mass of the conventional electrode.
[0037] The weight loss of the solidified electrode is obtained by the difference between the mass of the solidified electrode after heating to 600℃ and the mass of the solidified electrode. The weight loss rate t2 of the solidified electrode is obtained by the ratio of the weight loss of the solidified electrode to the mass of the solidified electrode.
[0038] SS3: X is obtained according to the following formula (5):
[0039] , (Formula 2).
[0040] As a further approach, a micrometer was used to measure the thickness of conventional and solidified electrodes, and the difference in thickness was calculated to obtain the change in electrode thickness ΔT before and after adding solid electrolyte monomers.
[0041] As a further method, the porosity ε of the solidified electrode can be obtained by mercury intrusion porosimetry.
[0042] As a further embodiment, the method for preparing solidified electrode sheets by polymer monomer homogenization is as follows: during the homogenization process, a prepolymer liquid containing polymer monomers and initiators is added to the electrode slurry, and after uniform stirring, they are homogenized together to obtain a slurry containing polymer monomers. The slurry containing polymer monomers is uniformly coated on the current collector, and solidified electrode sheets are obtained by thermal polymerization or ultraviolet polymerization.
[0043] In a second aspect, the present invention provides a method for screening solid-state batteries based on the method for predicting the degree of polymerization of solid-state electrode as described in the first aspect, wherein the porosity of the solid-state electrode is 4%≤ε≤17.5% and the degree of polymerization is 84%≤N≤97%; preferably, the predicted porosity of the solid-state electrode is 11%≤ε≤16% and the degree of polymerization is 90%≤N≤94%.
[0044] Based on the screening conditions of porosity and predicted degree of polymerization of the aforementioned solidified electrode, the porosity and degree of polymerization parameters obtained in this invention are the core basis for evaluating the final battery performance. Their main effects are on electrode expansion rate, active material specific capacity, and battery safety (such as performance in nail penetration tests). These effects are not isolated or direct, but rather achieved through a complex, multi-level physicochemical transmission mechanism.
[0045] On the one hand, the specific capacity of a battery depends on the transport efficiency of lithium ions and electrons within the electrode. Porosity indirectly reflects the challenges to the transport distance posed by electrode thickness and feed rate in this invention by affecting the tortuosity of the ion transport path: in low-porosity, high-compact electrodes, although interparticle electronic contact may be improved, the ion transport channel may be compressed, especially in thicker electrodes, where ion transport impedance becomes a limiting factor, resulting in insufficient capacity utilization; while in high-porosity, low-compact electrodes, although sufficient space is provided for ion transport, the contact points between active particles and conductive agents may decrease, the electron conduction network becomes sparse and discontinuous, and the lower compaction density may mean an increase in electrode thickness for the same areal capacity, which will also lengthen the electron conduction path, leading to increased ohmic polarization and limiting high-rate performance and capacity utilization. The degree of polymerization reflects the polymer monomer feed rate and electrode thickness in the polymerization degree prediction formula of this invention, which directly affects the ionic conductivity of the solid electrolyte itself and its interfacial contact with the active particles. Incomplete polymerization may leave behind a large number of polymer monomers or oligomers, forming network "islands" that affect ion transport; while proper polymerization can form a continuous ion transport network. The space provided by porosity is partially filled by the electrolyte, thus the pore structure under various factors and the conductivity of the polymer phase together constitute a "dual channel" for ion transport. Their synergistic effect determines the final lithium-ion flux, thereby affecting the specific capacity.
[0046] On the other hand, since thermal runaway behavior is closely related to the internal structural stability, thermal stability, and short-circuit current distribution of the electrode, the porosity defined in this invention reflects the compaction state and heat transfer characteristics of the electrode in this context. During needle puncture, the loose structure of a high-porosity, low-compact electrode results in weaker mechanical interlocking and electronic contact between particles, making short-circuit points easier to form. Furthermore, the initial short-circuit resistance may be low, triggering a large current surge. Simultaneously, the low thermal conductivity of the porous structure hinders heat diffusion along the in-plane direction, causing heat to accumulate rapidly near the puncture point, accelerating local temperature rise. The degree of polymerization reflects the amount of polymer monomers used and the electrode thickness variation in the polymerization degree prediction formula of this invention, which determines the thermal stability of the polymer network and its behavior at high temperatures. A highly polymerized cross-linked network has a higher thermal decomposition temperature, and the appropriate electrode thickness it reflects allows it to maintain mechanical integrity for a longer period under the high temperature at the moment of needle puncture, preventing the electrode structure from collapsing and causing a larger area of internal short circuit. Electrodes with low polymerization degree exhibit poorer thermal stability and are more prone to short circuits and heat accumulation. In addition, the change in electrode thickness reflected by the degree of polymerization affects the interfacial stability. Poorly polymerized interfaces may fail faster under thermal shock, exacerbating side reactions and thermal runaway.
[0047] On the other hand, there is a profound synergistic and restrictive relationship between porosity and the degree of polymerization. The space provided by the pore structure needs to be effectively filled and supported by polymer electrolytes or binders with appropriate mechanical properties. If the porosity is high but the degree of polymerization is insufficient, the polymer network strength is low, and the loose skeleton cannot fully utilize the pore space to build a stable load-bearing structure. It is still prone to collapse and densification during cycling, ultimately leading to expansion. Conversely, if the degree of polymerization is very high but the porosity is extremely low, the buffer space is insufficient, and the rigid polymer network may experience brittle cracking under huge volume change stress due to its inability to coordinate deformation. This will also damage the structure and exacerbate expansion. The aforementioned ranges of porosity and degree of polymerization further reflect the structural characteristics of the polymer, and can further obtain electrodes with lower expansion rates.
[0048] Therefore, porosity and degree of polymerization, as core predictive indicators, are valuable because they are the key to understanding the organic tandem electrode preparation parameters (such as feed rate, compaction density, and polymer selection), microstructural characteristics (such as thickness, pore network, and interface state), and macroscopic electrochemical and safety performance based on the prediction formula of this invention. By accurately predicting these two parameters, this invention can proactively infer the complex performance characteristics derived from or related to them, thereby achieving closed-loop prediction and optimization from electrode manufacturing to battery performance, greatly improving the targeting and efficiency of solid-state battery R&D.
[0049] The features and beneficial effects of this invention are as follows:
[0050] 1. This invention creatively establishes quantitative mathematical formulas relating the degree of polymerization to key measurable preparation parameters such as porosity (ε), polymer monomer addition amount (X), initial compaction density of the electrode (C), true density (TD), polymer monomer density coefficient (P), and thickness variation (ΔT). Without requiring complex direct chemical analysis, it utilizes readily available physical parameters during and after electrode preparation to achieve accurate and convenient prediction of the core state variable within the electrode—the degree of polymerization.
[0051] 2. Traditional point or surface sampling methods are difficult to reflect the gradient distribution of polymerization degree inside the electrode (such as in the thickness direction). The prediction method provided by this invention is essentially based on the overall average parameters of the electrode, and the result reflects the overall average polymerization degree of the electrode, effectively overcoming the problem of insufficient representativeness of local sampling, and providing a powerful tool for evaluating the uniformity and consistency of solidification processes.
[0052] 3. By limiting the range of key parameters, the model exhibits higher predictive reliability within the actual process window. Based on the predicted degree of polymerization and porosity, it can further effectively screen and predict the specific capacity utilization of active materials in electrode expansion, cycle expansion rate, and even battery safety performance (such as needle penetration pass rate), achieving cross-scale prediction from preparation parameters to battery end-use performance. Detailed Implementation
[0053] To facilitate understanding of the present invention, a more comprehensive description of the present invention will be given below, and embodiments of the present invention will be provided, but this does not limit the scope of the present invention.
[0054] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0055] The chemical raw materials used in the following examples and comparative examples are all prior art and commercially available. The experimental apparatus and testing equipment used in the following examples and comparative examples are all conventional equipment in the art, and there are no special requirements or limitations.
[0056] As a specific example of the implementation of this invention, detailed cases are provided below:
[0057] Solid-state electrodes were prepared according to the following schemes in Examples 1-17 and Comparative Examples 1-29:
[0058] Solidified electrodes were prepared using a polymer monomer homogenization method. During homogenization, a prepolymer solution containing 98.2–99.7% wt polymer monomers and 0.3–1.8% wt azo compound initiator was prepared. 0–25% wt of the prepolymer solution (containing binder, conductive agent, and active material) of the electrode dry materials was added to the electrode slurry (the lower limit was not 0%), and the mixture was stirred uniformly and homogenized together to obtain a slurry containing polymer monomers. This slurry was then processed at a concentration of 55 mg / cm³. 2 The areal density values on both sides are uniformly coated on the current collector, and solidified electrode sheets are obtained by thermal polymerization or ultraviolet polymerization. Polymerization is carried out at 50~80℃ for 20-48h, or ultraviolet polymerization at wavelengths of 365 / 385 / 405nm for 0.5~3min.
[0059] The electrode slurry includes a binder, a conductive agent, and a positive electrode active material; the mass ratio of the binder, conductive agent, and positive electrode active material in the electrode slurry is (0.8 ~ 3.0):(0.6 ~ 3.0):(94 ~ 98.6), the solvent of the electrode slurry is N-methylpyrrolidone, and the mass fraction of the binder, conductive agent, and positive electrode active material in the solvent is 65% ~ 75%.
[0060] The current collector, binder, conductive agent, positive electrode active material, polymer monomer, and initiator are not specifically limited.
[0061] As an example, the current collector is selected from any type of metal foil, specifically, it may be selected from aluminum foil / carbon-coated aluminum foil or copper foil / carbon-coated copper foil.
[0062] As an example, the adhesive is selected from one or more of polyvinylidene fluoride (PVDF), polyacrylic acid, polyacrylonitrile, and polyvinyl alcohol, and may be selected from PVDF5130, HSV900, etc.
[0063] As an example, the positive electrode active material is selected from nickel-cobalt-manganese ternary materials, and may be selected from one or more of the NCM622, NCM811, NCM83, and NCM9 series.
[0064] As an example, the polymer monomer is selected from one of acrylates, carbonates, fluorinated monomers, phosphorus-containing monomers, and ionic liquids.
[0065] As further examples, acrylate compounds include methyl methacrylate, ethyl acrylate, ethyl cyanoacrylate, polyethylene glycol diacrylate, diethylene glycol diacrylate, butyl acrylate, etc.; carbonates include ethylene ethylene carbonate, vinylene carbonate, propylene carbonate, etc.; fluorinated monomers include hexafluorobutyl methacrylate, hexafluorobutyl acrylate, octafluoropentyl acrylate, etc.; phosphorus-containing monomers include triallyl phosphate, diethyl allylphosphonate, etc.; ionic liquids include 1-vinyl-3-hexylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-vinyl-3-butylimidazolium bis(fluorosulfonyl)imide salt, 1-allyl-3-methylimidazolium hexafluorophosphate, etc.
[0066] As an example, the initiator is selected from one of organic peroxides, α-hydroxy ketones, and acylphosphine oxides; specifically, it may be selected from one of AIBN, AIBME, TPO, and 819.
[0067] As an example, the prepolymer solvent is selected from one of acetonitrile, ethanol, acetone, methanol, ethylene glycol dimethyl ether, dimethyl carbonate, tetrahydrofuran, N,N-dimethylformamide, chloroform, and N-methylpyrrolidone.
[0068] C represents the conventional compaction density of the slurry without prepolymer solution after coating and rolling, while TD represents the true density of the components contained in the conventional electrode sheet, which can be obtained through conventional testing methods in this field.
[0069] Solid-state batteries are assembled by combining solid-state positive electrode sheets with graphite / silicon negative electrode sheets, semi-solid electrolyte, and conventional PP / PE separators.
[0070] The following tests and calculations were performed on Examples 1-17 and Comparative Examples 1-29 described above:
[0071] X is obtained through the weightlessness method, specifically including the following steps:
[0072] SS1: During the homogenization process, a prepolymer solution containing polymer monomers and initiators is added to the electrode slurry for homogenization to obtain a slurry containing polymer monomers. The slurry containing polymer monomers is then uniformly coated onto the current collector. After polymerization, a solidified electrode is obtained and weighed.
[0073] The positive electrode sheet produced by uniformly coating the electrode slurry onto the current collector, drying, and rolling is a conventional electrode sheet, which is then weighed.
[0074] SS2: Both solid-state electrode and conventional electrode were heated from room temperature to 600℃ at a rate of 10℃ / min under an inert gas atmosphere, and weighed separately;
[0075] The weight loss of the conventional electrode is obtained by the difference between the mass of the conventional electrode after heating to 600℃ and the mass of the conventional electrode. The weight loss rate t1 of the conventional electrode is obtained by the ratio of the weight loss of the conventional electrode to the mass of the conventional electrode.
[0076] The weight loss of the solidified electrode is obtained by the difference between the mass of the solidified electrode after heating to 600℃ and the mass of the solidified electrode. The weight loss rate t2 of the solidified electrode is obtained by the ratio of the weight loss of the solidified electrode to the mass of the solidified electrode.
[0077] SS3: X is obtained according to the following formula (5):
[0078] , (Formula 2).
[0079] The thickness T of the electrode before the polymer monomer was added and the thickness T2 of the solidified electrode were measured using a Mitutoyo digital micrometer. The difference in thickness, ΔT, between T2 and T was calculated to obtain the change in electrode thickness before and after polymer monomer coating. C2 represents the areal density of the solidified electrode. The true density TD of the electrode before the addition of polymer monomers to the slurry was obtained by gas gravity method using an Ultra PYC 1200e true density analyzer, referring to GB / T 5071-2013 "True Density Test Method for Refractory Materials".
[0080] The porosity ε of solidified electrodes can be obtained by mercury intrusion porosimetry.
[0081] A 5cm x 5cm sample is cut, rolled into a strip, and placed into a special sealed container for testing, usually a mercury-sealed pressure chamber. The pressure chamber is then installed on a mercury porosimeter, and room-temperature mercury is injected. The pressure in the chamber is gradually increased, causing the pores in the electrode to be gradually filled with mercury. The greater the external pressure, the smaller the radius of the pores that mercury can enter. Finally, the electrical signal generated by the mercury entering the sample pores during the mercury porosimeter process is processed to simulate relevant spectra and calculate the porosity data.
[0082] The polymerization degree prediction method is to calculate the predicted polymerization degree N of the solidified electrode using the following formula (1):
[0083] , formula (1);
[0084] Where X is the amount of polymer monomer added, which is the ratio of the mass of polymer monomer added to the total mass of the electrode slurry, and the electrode slurry does not include polymer monomer; C is the compacted density of the electrode before the polymer monomer is added to the slurry; TD is the true density of the electrode before the polymer monomer is added to the slurry; ΔT is the change in electrode thickness before and after the polymer monomer is added to the slurry; ε is the porosity of the solidified electrode, and the polymer monomer density coefficient P is the density ratio of polymer monomer to polyethylene glycol diacrylate at a temperature of 25°C.
[0085] The solid-state battery screening method based on the method for predicting the degree of polymerization of the solid-state electrode has a porosity of 4%≤ε≤17.5% and a degree of polymerization of 84%≤N≤97%; preferably, the predicted porosity of the solid-state electrode is 11%≤ε≤16% and the degree of polymerization is 90%≤N≤94%.
[0086] Taking Example 1 as an example, the preparation method of the solidified electrode is as follows:
[0087] Solidified electrodes were prepared using a polymer monomer homogenization method. During homogenization, a prepolymer solution containing 99.5% wt polymer monomers and 0.5% wt azo initiator was prepared. This prepolymer solution was added to the electrode slurry, and the mixture was stirred and homogenized together to obtain a slurry containing polymer monomers. The mass ratio of monomers to dry matter in the slurry was 18:100. This slurry was uniformly coated onto a current collector, and solidified electrodes were obtained by thermal polymerization or UV polymerization. Polymerization was carried out at 80℃ for 24 hours.
[0088] The electrode slurry includes PVDF binder, Super P and CNT conductive agents, and NCM811 positive electrode active material; the mass ratio of binder, conductive agent and positive electrode active material in the electrode slurry is 1.3:1.2:97.5, the solvent of the electrode slurry is N-methylpyrrolidone, and the mass fraction of the binder, conductive agent and positive electrode active material in the solvent is 70%.
[0089] C represents the conventional compacted density of the slurry without prepolymer solution after coating and rolling, while TD represents the true density of the components in a conventional electrode, which can be obtained using conventional testing methods in this field. In this embodiment, the specific value of C measured is 3.3 g / cm³. 3 TD is 4.635 g / cm³ 3 .
[0090] The thickness of conventional and solidified electrodes was measured using a Mitutoyo digital micrometer, and the difference in thickness was calculated to obtain the change in electrode thickness ΔT before and after coating with solid electrolyte monomer. ΔT is 1.5 μm.
[0091] Solid-state batteries are assembled by combining solid-state positive electrode sheets with graphite / silicon negative electrode sheets, semi-solid electrolyte, and conventional PP / PE separators.
[0092] X is obtained through the weightlessness method, specifically including the following steps:
[0093] SS1: During the homogenization process, a prepolymer solution containing polymer monomers and initiators is added to the electrode slurry for homogenization to obtain a slurry containing polymer monomers. The slurry containing polymer monomers is then uniformly coated onto the current collector. After polymerization, a solidified electrode is obtained and weighed.
[0094] The positive electrode sheet is manufactured by uniformly coating the electrode slurry onto the current collector and drying it. It is then weighed.
[0095] SS2: Both solid-state electrode and conventional electrode were heated from room temperature to 600℃ at a rate of 10℃ / min under an inert gas atmosphere, and weighed separately;
[0096] The weight loss of the conventional electrode is obtained by the difference between the mass of the conventional electrode after heating to 600℃ and the mass of the conventional electrode. The weight loss rate t1 of the conventional electrode is obtained by the ratio of the weight loss of the conventional electrode to the mass of the conventional electrode.
[0097] The weight loss of the solidified electrode is obtained by the difference between the mass of the solidified electrode after heating to 600℃ and the mass of the solidified electrode. The weight loss rate t2 of the solidified electrode is obtained by the ratio of the weight loss of the solidified electrode to the mass of the solidified electrode.
[0098] SS3: X is obtained according to the following formula (2):
[0099] , (Formula 2).
[0100] Thermogravimetric analysis showed that t1 was 1.68% and t2 was 16.68%, and X was calculated to be 18.0%.
[0101] The porosity ε of the solidified electrode was determined to be 12.48% by mercury porosimetry.
[0102] A 5cm x 5cm sample is cut, rolled into a strip, and placed into a special sealed container for testing, usually a mercury-sealed pressure chamber. The pressure chamber is then installed on a mercury porosimeter, and room-temperature mercury is injected. The pressure in the chamber is gradually increased, causing the pores in the electrode to be gradually filled with mercury. The greater the external pressure, the smaller the radius of the pores that mercury can enter. Finally, the electrical signal generated by the mercury entering the sample pores during the mercury porosimeter process is processed to simulate relevant spectra and calculate the porosity data.
[0103] The polymerization degree prediction method is to calculate the predicted polymerization degree N of the solidified electrode using the following formula (1):
[0104] , formula (1);
[0105] Where X represents the amount of polymer monomer added, which is the ratio of the mass of polymer monomer added to the total mass of the electrode slurry, excluding the polymer monomer; C represents the compacted density of the electrode before the addition of polymer monomer; TD represents the true density of the electrode before the addition of polymer monomer; ΔT represents the change in electrode thickness before and after the addition of polymer monomer; ε represents the porosity of the solidified electrode; and the polymer monomer density coefficient P is the density ratio of polymer monomer to polyethylene glycol diacrylate at 25°C, where P is 1. The obtained N is 91.55%.
[0106] The degree of polymerization can be verified using an extraction method. The verification method is as follows: the solidified electrode prepared in the above examples is extracted n times. For each extraction, the solidified electrode is placed in acetonitrile (2g of W2) as the extraction solvent until the mass fraction of uncured polymer monomers detected in the extraction solution is ≤0.1%. Extraction is then stopped, and a polymerization inhibitor MEHQ is added according to the polymer monomer type (poly(ethylene glycol) diacrylate). The polymerization inhibitor accounts for 0.01% of the mass in the extraction solvent. After ultrasonication for 10 minutes under sealed conditions at 20-25℃, the solution is soaked for 8 hours to obtain the extraction solution. The same amount (2g) of extraction solvent is used for each extraction. The mass fraction mi of uncured polymer monomers in the extraction solvent is obtained by gas chromatography-mass spectrometry (GC-MS). In this example, m1 is 0.38%, m2 is 0.25%, m3 is 0.11%, and m4 is 0.04%. The degree of polymerization N of the solidified electrode is calculated using formula (F1). Where A is the solvent evaporation coefficient, which is the ratio of the mass of the extraction solvent that evaporates to the mass of the extraction solvent after being placed in a sealed box for 5 days at 1 standard atmosphere at room temperature. When the extraction solvent is acetonitrile, A is 1.9%; when the extraction solvent is isopropanol, A is 1.3%; when the extraction solvent is dichloromethane, A is 10.2%; and when the extraction solvent is n-propanol, A is 1%.
[0107] The following tests were performed on Examples 1-17 and Comparative Examples 1-29:
[0108] Electrode swelling rate: After being soaked in electrolyte for 24 hours, the solidified electrode will swell and its thickness will increase. The thickness data of the solidified electrode before and after soaking is tested, and the ratio of the thickness difference to the thickness before soaking is the electrode swelling rate.
[0109] Positive electrode specific capacity test: The shipped battery cell is charged and discharged at 0.1C. The ratio of the 0.1C discharge capacity to the mass of the positive electrode material is the specific capacity data of the positive electrode.
[0110] Needle penetration test: At 25±3℃, a steel nail is inserted into the center of a fully charged fresh battery cell at a speed of 150 mm / s until it is completely penetrated. The nail is held for 10 minutes and then withdrawn. The diameter of the steel nail is 4±0.06 mm. After the test is completed, the combustion and temperature data during the needle penetration process are recorded.
[0111] The data obtained from the above tests for Examples 1-17 and Comparative Examples 1-29 are shown in Table 1 below.
[0112] Table 1
[0113]
[0114]
[0115] Table 2 shows the comparison between the degree of polymerization N obtained by the extraction method in Examples 1-17 and Comparative Examples 1-29 and the N calculated by formula (1).
[0116] Table 2
[0117]
[0118]
[0119] As can be seen from Examples 1-17 and Comparative Examples 1-29, the polymerization degree prediction formula established in this invention and the battery screening parameter range set based on the formula have been fully verified. Table 1-2 shows that the theoretical polymerization degree N calculated based on the formula in all examples and comparative examples is basically consistent with the value of polymerization degree N obtained by the extraction method, with an absolute deviation of ≤2.5%.
[0120] Using the porosity ε of the solidified electrode and the predicted degree of polymerization N to screen for comprehensive battery performance, Examples 1-17 show that when 4%≤ε≤17.5% and 84%≤N≤97%, the battery exhibits a lower expansion rate, higher specific capacity of the positive electrode active material, and the assembled batteries all perform excellently in nail penetration tests. This confirms that the degree of polymerization and its parameter combination obtained under this formula can effectively synergistically regulate the ion / electron transport network, interface stability, and mechanical structure integrity, thereby comprehensively optimizing the electrochemical and safety performance of the battery.
[0121] The data from Comparative Examples 1 to 29 show that when ε and / or N deviate from the above-mentioned preferred ranges, one or more key performance indicators of the battery deteriorate significantly. For example, a low degree of polymerization N is usually accompanied by poor safety; while a low porosity ε may lead to runaway expansion and deterioration of electronic conduction, resulting in reduced capacity utilization.
[0122] As can be seen from the comparison of Examples 1-5 and 7 with other examples, the present invention further sets the solid-state battery screening method to 11%≤ε≤16% and 90%≤N≤94%, resulting in higher positive electrode specific capacity and better needle penetration pass rate, while controlling the electrode expansion rate at a lower level. This indicates that the combination of the above parameters represents a more precise balance between ion transport channels, electron conduction networks, and polymer structural stability.
[0123] These results clearly demonstrate that the polymerization degree prediction method provided by this invention not only possesses theoretical innovation but also has extremely strong engineering guidance value. It correlates the internal reaction state (polymerization degree), which is difficult to measure directly, with easily obtainable preparation parameters and macroscopic physical properties (porosity, thickness variation, etc.), and successfully defines a key parameter window corresponding to excellent overall performance. This shows that the formula can fully reflect the coupling relationship between the initial electrode pore state, monomer filling level, and polymerization kinetics, forming a comprehensive prediction tool that profoundly reflects the essence of the solid-state process. This provides a powerful tool for the quantitative design of solid-state electrode quality, precise process control, and reliable prediction of battery performance, which will greatly improve the R&D efficiency and product consistency of polymer solid-state batteries, and is of great significance for promoting their industrialization.
[0124] The technical features of the embodiments described above can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the invention. Those skilled in the art can make modifications, alterations, substitutions, and variations to the above embodiments within the scope of the present invention. Furthermore, without contradiction, those skilled in the art can combine and integrate different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
Claims
1. A method for predicting the degree of polymerization in the preparation of solidified electrodes using a polymer monomer homogenization method, characterized in that, The polymerization degree prediction method is to calculate the polymerization degree prediction value N of the solidified electrode using the following formula (1): Formula (1); Where X is the amount of polymer monomer added, which is the ratio of the mass of polymer monomer added to the total mass of active material, conductive agent and binder in the preparation of solidified electrode sheet; C is the compaction density of the electrode sheet before the polymer monomer is added to the slurry; TD is the true density of the electrode sheet before the polymer monomer is added to the slurry; ΔT is the change in thickness of the electrode sheet before and after the polymer monomer is added to the slurry; ε is the porosity of the solidified electrode sheet; and the polymer monomer density coefficient P is the density ratio of polymer monomer to poly(ethylene glycol) diacrylate at a temperature of 25°C. The unit of measurement for C is g / cm³. 3 The unit of measurement for TD is g / cm³. 3 The unit of measurement for △T is μm.
2. The method for predicting the degree of polymerization of solidified electrodes prepared by polymer monomer homogenization according to claim 1, characterized in that, In the formula (1), 2.8≤C≤3.6, 0%<ε≤30%, and 0≤X≤25%.
3. The method for predicting the degree of polymerization in the preparation of solidified electrodes using the polymer monomer homogenization method according to claim 1, characterized in that, X in formula (1) can be obtained by the weightlessness method, specifically including the following steps: SS1: During the homogenization process, a prepolymer solution containing polymer monomers and initiators is added to the electrode slurry for homogenization to obtain a slurry containing polymer monomers. The slurry containing polymer monomers is then uniformly coated onto the current collector. After polymerization, a solidified electrode is obtained and weighed. The positive electrode sheet is produced by uniformly coating the electrode slurry onto the current collector, drying it, and then rolling it to produce a conventional electrode sheet, which is then weighed. SS2: Both solid-state electrode and conventional electrode were heated from room temperature to 600℃ at a rate of 10℃ / min under an inert gas atmosphere, and weighed separately; The weight loss of the conventional electrode is obtained by the difference between the mass of the conventional electrode after heating to 600℃ and the mass of the conventional electrode. The weight loss rate t1 of the conventional electrode is obtained by the ratio of the weight loss of the conventional electrode to the mass of the conventional electrode. The weight loss of the solidified electrode is obtained by the difference between the mass of the solidified electrode after heating to 600℃ and the mass of the solidified electrode. The weight loss rate t2 of the solidified electrode is obtained by the ratio of the weight loss of the solidified electrode to the mass of the solidified electrode. SS3: X is obtained according to the following formula (2): (Official 2).
4. The method for predicting the degree of polymerization of solidified electrodes prepared by polymer monomer homogenization according to claim 1, characterized in that, The thickness of conventional and solidified electrodes was measured using a micrometer, and the difference in thickness was calculated to obtain the change in electrode thickness ΔT before and after adding solid polymer monomers.
5. The method for predicting the degree of polymerization of solidified electrodes prepared by polymer monomer homogenization according to claim 1, characterized in that, The porosity ε of solidified electrodes can be obtained by mercury intrusion porosimetry.
6. The method for predicting the degree of polymerization in the preparation of solidified electrodes using the polymer monomer homogenization method according to claim 1, characterized in that, The method for preparing solidified electrode sheets by polymer monomer homogenization is as follows: during the homogenization process, a prepolymer liquid containing polymer monomers and initiators is added to the electrode slurry, and after uniform stirring, they are homogenized together to obtain a slurry containing polymer monomers. The slurry containing polymer monomers is uniformly coated on the current collector, and solidified electrode sheets are obtained by thermal polymerization or ultraviolet polymerization.
7. The application of formula (1) in the method for predicting the degree of polymerization of solid-state electrode as described in any one of claims 1 to 6 in the screening of solid-state batteries, characterized in that, The porosity of the solidified electrode is 4%≤ε≤17.5%, and the degree of polymerization is 84%≤N≤97%.
8. The application according to claim 7, characterized in that, The predicted porosity of the solidified electrode is 11%≤ε≤16%, and the degree of polymerization is 90%≤N≤94%.
